Post-Activation Performance Enhancement in Badminton Players: A Randomized Crossover Study Comparing the Acute Effects of Four Squat Protocols on CMJ Performance - Dhaka, Shubham; Sahu, Manoj; Sonowal, Kapi; Upadhyay, Kautilya; Terang, Varun; Singh, Vikas; Singh, Sangram (Physical Education Theory and Methodology, 2026)
Objectives. The objective of this study was to compare the acute post-activation performance enhancement (PAPE) effects of four squat-based conditioning protocols—bodyweight squats, BOSU-ball squats, resistance-band squats, and weighted-vest squats—on countermovement jump (CMJ) performance in trained badminton players. Materials and Methods. Twelve competitive badminton players (8 males, 4 females; age 21.5 ± 2.1 years) with a minimum of five years of playing experience participated in this randomized crossover study. Each athlete completed all four squat protocols in a counterbalanced order, separated by 48-hour washout periods. CMJ height was measured at baseline and at 4, 8, and 12 minutes post-conditioning using an inertial motion sensor (BTS G-Walk, Italy). A two-way repeated-measures ANOVA (Protocol × Time) with Bonferroni-adjusted comparisons was applied to determine the effects of each protocol and recovery interval on CMJ height. Results. Significant main effects of Protocol (p = .001), Time (p = .004), as well as a significant Protocol × Time interaction (p < .001), were observed. The weighted-vest protocol produced the greatest PAPE response, with CMJ height increasing from 29.7 ± 0.9 cm at baseline to 33.2 ± 0.8 cm at 8 minutes (an 11.8% improvement; p < .01). The resistance-band protocol elicited a moderate enhancement, peaking at 31.1 ± 1.3 cm at 8 minutes (p < .05). Bodyweight and BOSU-ball squats produced minimal, non-significant variations in CMJ performance. The 8-minute interval consistently yielded the highest potentiation across the effective protocols. Conclusions. Squat-based conditioning activities using external loading—particularly weighted-vest squats—induce superior post-activation performance enhancement in badminton players compared with bodyweight or unstable-surface squats. The findings indicate that a recovery interval of approximately eight minutes optimizes CMJ potentiation. Weighted-vest squats may therefore be recommended as an effective pre-competition activation strategy for improving explosive lower-limb performance in badminton athletes.